Sedentary time of university students before and during the COVID-19 pandemic: Risk groups and pre-pandemic predictors using cross-sectional and longitudinal data - Heller, Sebastian; Kalo, Kristin; Werner, Antonia M.; Eisenbarth, Laura; Reichel, Jennifer L.; Mülder, Lina M.; Schäfer, Markus; Letzel, Stephan; Simon, Perikles; Rigotti, Thomas; Dietz, Pavel (Frontiers in Public Health, 2023)
Background: The present study aimed to (1) assess and compare sedentary time (ST) of university students before and during the COVID-19 pandemic, (2) examine risk groups with regard to ST and the “extent of change” in ST (from before to during the pandemic) in association with sociodemographic (gender, age), study-related (degree aspired to, field of study, semester), and prepandemicpre-pandemic physical health-related [prepandemicpre-pandemic physical activity (PA) and ST levels, prepandemicpre-pandemic BMI class] variables, and (3) investigate whether the change in ST was predicted by these variables. Methods: Two online surveys were conducted among students at the University of Mainz, Germany—the first in 2019 (before the pandemic, N=4,351) and the second in 2020 (during the pandemic, N=3,066). Participants of both surveys were included in a longitudinal sample; N=443 participated in both surveys and were included in the longitudinal sample. With the longitudinal sample’s data, paired t-tests, single factor, and mixed analyses of variances were used to examine group differences in ST and the “extent of change” in ST. A linear regression analysis was computed to investigate the influence of the abovementioned sociodemographic, study-related, and pre-pandemic physical health-related variables on the change in ST. Results: Of the N=4351 (pre-pandemic) and N=3,066 (in-pandemic) participants of the online surveys, N=443 entered the longitudinal sample. ST increased by 1.4 hours/day to critical levels (≥8 hours/day) in all subgroups analyzed—even among students who were highly physically active before the pandemic. Students with a low prepandemicpre-pandemic ST had the largest increase in ST. PrepandemicPre-pandemic PA level negatively predicted the change in ST. Conclusion: Even during a global pandemic lockdown, individuals who were previously more physically active and had less ST showed more health-promoting behavior in terms of ST. Therefore, Eit can be stated that efforts to promote PA and reduce ST are always valuable., since even during a global pandemic lockdown, individuals who were previously more physically active and had less ST showed more health-promoting behavior in terms of ST. Since ST increased and was worryingly high in all subgroups analyzed, all university students should be targeted by multidimensional approaches to tackle ST and promote their health.